Cadmium zinc telluride pixel detectors for high-intensity x-ray imaging at free electron lasers. (24th December 2018) - Veale, M C; Angelsen, C; Booker, P; Coughlan, J; French, M J; Hardie, A; Hart, M; Lipp, J; Nicholls, T; Schneider, A; Seller, P; Sole, D; et al.
Abstract: This paper reports the first demonstration of high-intensity x-ray imaging using cadmium zinc telluride (CdZnTe) pixel detectors at a free electron laser (FEL). Prototype detectors were produced using the STFC large pixel detector (LPD) ASIC and sensors fabricated from a novel high-intensity-capable CdZnTe material produced by Redlen Technologies. Characterisation of the performance of this sensor material was completed at the Linac Coherent Light Source (LCLS) FEL. The detectors were operated at a frame rate of 1 MHz with 9.5 keV x-ray pulses delivered at a rate of 120 Hz. Measurements successfully demonstrated the linear response of the CdZnTe material to increasing numbers of x-rays up to a fluence of 8 GeV mm −2 per pulse, the limit of the dynamic range of the LPD ASIC.